PRODUÇÃO DE BERINJELA (Solanum melogena L.) EM DIFERENTES AMBIENTES E MATERIAL REFLETOR EM BANCADA - VIEIRA, Mariane Tavares; SOUZA, Larissa Gabriela Pereira; ALVES, Vitória Carolina Dantas; MARQUES, Ana Letícia Ribeiro; COSTA, Edilson (ANAIS DO ENIC, 2020)
-